Fostering a Climate of Inclusion in the College Classroom The Missing Voice of the Humanities - Lovern, Lavonna L. (Springer International Publishing, 2018)
This book examines inclusion teaching at the college and university level. It establishes the importance of the Humanities disciplines and the use of qualitative analysis as a means of understanding and encouraging democratic materials and classroom organization. The first section of the text provides two primers for those unfamiliar with pedagogical history and theory. These primers are designed to give basic information and sources for additional study. They trace pedagogical influences from foundationism, neoliberalism, conflict, and critical theories to critical race theory, Red pedagogy, and decolonization theories. The second half of the book focuses on strategies to assist those attempting classroom inclusion. These chapters are designed to assist with practical ways in which inclusion can be advanced as well as strategies to assist junior faculty in the navigation of the politics of inclusive education. .